Perubahan Tatanan Hijab Mahasiswi Muslimah: Analisa Motif Dan Ideologi Keislaman - Wahyuningsih, Sri (FIKRAH, 2017)
This article mainly describes the changes of hijab and fashion shown females students regarding to their motives and Islamic ideology. This study used a qualitative method applying a social learning theory of Albert Bandura. In-depth interviews and documentation used to collect the data. The results showed that the students had a process of imitation in terms of hijab and fashion worn by others. They observed hijab and fashion (attention). The styles of hijab and fashion they noticed is then stored (retention). Then, they began to wear the hijab and clothing with new models (reproduction). Their new appearance is a form of motivation. Some of them argued that Islamic values and faith are the affairs of every person with God and a fashionable style is a woman's choice. Meanwhile, other students thought that both fashionable style and essential functions aspects of hijab should be integrated well.